Interferon Lambda: An Anonymous Warrior of Host-Microbial Fray in The Pathogenesis of Periodontal Diseases - Ahmed, Muzammil Moin (Bangladesh Journal of Medical Science, 2024)
The current body of research focuses primarily on three fundamental groups of interferons: alpha, beta, and gamma interferons. However, little attention is paid to another important group of interferons called lambda interferons (IFN-λs), which have demonstrated activity against periodontal pathogens, particularly viruses. These recently discovered interferon-lambdas provide a striking contrast to the periodontal pathogens, exerting impact both at the capacity of the immune system and the cell, thereby affecting a variety of inflammatory and response pathways. Thus, this review sheds light on role of interferon lambda in the development of periodontal disease and associated activities. In order to collect the information necessary for this review, an exhaustive search of the relevant literature was conducted. The review focused on the structure, regulatory mechanisms, and role of interferon lambda in medical and periodontal infections and diseases. The findings of our review indicated that IFN-λs have an effect on the immunological regulatory mechanisms of the host in relation to viruses, bacteria, fungi, and parasites; nevertheless, their primary role is antiviral, and they have little to no effect on the immune system's ability to fight bacteria. Bangladesh Journal of Medical Science Vol.23 (Special Issue) 2024 p.S73-S78